f(x)=x^3-6x^2+2x-4 is divided by y(x)=3x-1 find remainder
Answers
Answered by
1
Answer:
solution, f(x)=x³-6x²+2x-4
divisior y(x)=3x-1 comparing with x-k
=3k=1
k=1/3
f(k)=1/3³-6×1/3²+2×1/3-4
=1/27-6×1/9+2/3-4 (multiplying 6 into 1/2)
=1/27-2/3+2/3-4( 2/3 is cancelled)
=1/27-4
=1-108/27
=-107/27
hope it's helpful
mark me as brainliest
Similar questions
English,
2 months ago
Social Sciences,
2 months ago
Math,
2 months ago
Biology,
4 months ago
English,
4 months ago
Biology,
1 year ago
Computer Science,
1 year ago